Tax at a Glance for ECA Countries - World Bank (Washington, DC, 2014)
The tax-at-a-glance provides an overview of the tax policy and tax administration system as well as main trends in tax reform for each Europe and Central Asia (ECA) country. In the ECA region, two historic transitions since 1990 (a political transition from totalitarianism toward democracy and an economic transition from socialism toward free market systems) required a fundamental change in the role of the state, from controlling virtually all major economic assets to providing public goods and facilitating a largely privately-owned competitive economy. This change in the role of the state required a major downsizing and reorientation of public spending and a complete overhaul of tax policy and administration. Formidable challenges existed in setting up an efficient and fair tax system in ECA. First, voluntary compliance and self-filing, two important pillars in a modern tax system, were completely absent. Second, tax evasion reached a high level due to the inefficiency and weak management of the tax administration. Third, income was unevenly distributed within ECA countries. The economic and political power of rich taxpayers prevented tax reforms and this partially led to inefficient and unfair tax systems. Fourth, tax administration was very inefficient, with a poorly educated and poorly trained staff. Modern technologies had not been fully deployed in tax offices. Due to administrative and financial limitations, statistical and tax offices have difficulty in providing reliable statistics. Furthermore, low level of transparency in several tax administrations in ECA countries makes it harder to collect accurate information on tax performance. The poor quality of data often prevents policymakers and economists from assessing potential problems and challenges to existing tax systems.